Is ethics a science? - Zecha, Gerhard (Folia Philosophica, 2001)
Like many philosophers today, Sir Karl R. Popper asserts: “Ethics is not a science.” Three arguments are described with which Popper supports his claim: (1) the dualism between facts and standards; (2) the idea of truth is not applicable to standards; (3) the so-called scientific ethics kills the personal responsibility of humans. Against these suggestions, the author argues that the dualism between facts and standards can be overcome with simple „bridging principles”; parallel to the idea of truth in the sciences there is the regulative idea of life, protection and fulfillment of life - albeit with one decisive difference: whereas the scientist can reach only an approximation to truth which makes him criticize and revise scientific findings, the value of life can be reached and can be realized. Life as both the foundation and goal of ethics makes it more than a mere science, it makes ethics a part of wisdom. Ethics is science as well, because the critical method, learning and testing by trial and error, is applicable in ethics as it is in science, and is, when properly used, strengthening personal responsibility.